Observations on the ecology of the freshwater leech helobdella stagnalis (hirudinoidea: glossiphoniidae), new for turkey - Sağlam, Naim; Dörücü, Mustafa (My University, 2002)
The freshwater leech Helobdella stagnalis was found in fish ponds and discharge channels at a Fisheries Research Station near Elazığ on the Upper Euphrates. It was identified on the basis of morphological features. The species had not previously been recorded in Turkey. The abundance of the species was highest (1.3±0.07 leeches/m²) in August and lowest (0.2 leeches/m²) in February. © 2002 Taylor & Francis Group, LLC.
Keywords: Abundance; Leech morphology; Middle East; Phenology; Turkey